Assessing the acceptance and aesthetics of unmanned aerial vehicles (drones): An experimental and survey-based comparison between students and older adults - Svantje T. Kähler; Miriam Tomat; Aquiles Luna-Rodriguez; Thomas Jacobsen (Transportation Research Interdisciplinary Perspectives, 2025)
Contextual effects and comparisons of technologies to their alternatives (e.g., drones and helicopters) provide the industry, regulators, and other stakeholders with valuable information for more effective participation by communities that are overflown. We present older adults’ (a significant proportion of Western societies) acceptance and beauty ratings of visual stimuli depicting flying quadcopters, replicate and compare these results with those of a previous student study, and overall validate the benefits of experimental approaches for assessing acceptance of Advanced Aerial Mobility (AAM). The stimuli depicted quadcopters with medical or commercial markings, with helicopters and geese used as controls. We tested environmental effects on the ratings by superimposing these objects on urban, industrial, or rural backgrounds and also assessed participants’ knowledge and experience of drones and the reasons for their acceptance ratings.Only the students’ acceptance ratings were dependent on the environment, the different objects, and the salience of the objects. For older demographic groups, the usage alone may determine acceptance—although not all participants were familiar with the medical usage of AAM. The self-assessed factors behind the acceptance ratings indicated that “usefulness” was the most important factor for both groups, followed by “environment” (which was more important for the older adults). As the simultaneous experimental assessment of different factors’ impact on AAM acceptance yielded valuable information about their importance and the interaction of effects, industries and policymakers should consider the contextual factors and visual effects of AAM, along with other nontechnical variables.